Digital Payment Experience: The Influence of Hedonic Motivation and Price Value on QRIS Usage Intention - I Nyoman Budiarta; Komang Endrawan Sumadi Putra (Lembaga Riset dan Inovasi Al-Matani, 2025)
QRIS is a digital payment system innovation in the form of a standardized QR Code launched by Bank Indonesia with the aim of making transactions more practical and faster. This study aims to determine the influence of hedonistic motivation and price value on the interest in using QRIS as a payment gateway among students at the Faculty of Economics, Ganesha University of Education. The research method used is an associative quantitative approach. The research sample consisted of 100 respondents selected using purposive sampling techniques. Data was collected through a Likert scale questionnaire and analyzed using multiple linear regression with the assistance of SPSS software. The results of the study indicate that hedonic motivation has a positive and significant effect on interest in using QRIS. Price value has also been proven to have a positive and significant effect on interest in using QRIS. Thus, it can be concluded that the higher the hedonic motivation and the greater the perceived price value, the higher the interest of students in using QRIS as a digital payment tool.